(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In order to further improve the quality of education in higher education institutions, it is necessary to pay attention to the management of educational activities. A number of issues such as the creation of a national system of knowledgeable, highly qualified, competitive, entrepreneurial personnel at the level of developed countries, a deep understanding of the psychological aspects of education, the search for new forms and consistent ways for learners to acquire independent knowledge, and the creation of a psychological system for managing educational activities for learners , requires the development of new methods of organizing educational training, further improvement of the methods used. In this context, a model of innovative training management functions was developed.